PeriAnesthesia nursing core curriculum : preprocedure, phase I and phase II, PACU nursing /: preprocedure, phase I and phase II, PACU nursing. (2016) - Schick, Lois; Windle, Pamela E; American Society of PeriAnesthesia Nurses,
No abstract available